OP14 Improved endoscopic outcomes and mucosal healing of upadacitinib as an induction therapy in adults with moderately to severely active ulcerative colitis: data from the U-ACHIEVE study. (25th January 2019) - Sandborn, W J; Schreiber, S; Lee, S D; Lindsay, J O; Hebuterne, X; Zhou, W; Cataldi, F; Lacerda, A P; Huang, B; Xie, W; Loftus Jr, E V
Abstract: Background: The efficacy and safety of upadacitinib, an oral, selective Janus Kinase 1 inhibitor, was assessed in an 8-week Phase 2 induction study of patients with moderately to severely active ulcerative colitis who had inadequate response, loss of response or intolerance to corticosteroids, immunosuppressants, or biologic therapies. 1 This analysis evaluated the endoscopic improvement, endoscopic remission, histological improvement, histological remission, and mucosal healing rates at Week 8 of the U-ACHIEVE study. Methods: Adult patients with Adapted Mayo Score (Mayo score without Physician Global Assessment) of 5–9 points and centrally read endoscopy subscore of 2–3 were randomised to receive extended-release upadacitinib 7.5, 15, 30, 45 mg once daily (QD) or placebo for 8 weeks. Patient randomisation was stratified by previous biologic use, baseline corticosteroid use, and baseline Adapted Mayo score (≤7/>7). The proportion of patients who achieved endoscopic improvement (endoscopic subscore ≤1), endoscopic remission (endoscopic subscore of 0), histological improvement (any decrease from baseline in Geboes score), histological remission (Geboes score <2), and mucosal healing (endoscopic subscore of 0 AND Geboes score <2) were analysed and pairwise comparisons between upadacitinib doses and placebo were conducted using the Cochran–Mantel–Haenszel test stratified by randomisation factors. Non-responder imputation was utilised for missing values. Results: A total of 250 patients were randomised with a mean (SD) age of 42.3 (14.2) years and a mean (SD) disease duration of 8.2 (2.5) years. At baseline, 77.6% had prior use of biologics, 36% had an Adapted Mayo Score >7, and 79% had an endoscopic subscore of 3. At Week 8, a dose–response relationship was observed for all efficacy endpoints. The proportion of patients achieving endoscopic improvement, endoscopic remission, histological improvement, histological remission, and mucosal healing was statistically significantly higher ( p < 0.05) in the upadacitinib 30 and 45 mg QD groups vs. the placebo group (Table). Conclusions: In this dose-ranging 8-week induction study, upadacitinib 30 and 45 mg QD consistently demonstrated significant improvement in endoscopic outcomes, histological outcomes, and mucosal healing compared with placebo in patients with moderately-to-severely active ulcerative colitis. Reference 1. Sandborn WJ. Efficacy and safety of upadacitinib as an induction therapy for patients with moderately-to-severely active ulcerative colitis: data from the phase 2b study U-ACHIEVE, United European Gastroenterology (UEG) Week, Presentation #OP195, 2018.